ANGKATAN OEMAT ISLAM 1945-1950 STUDI TENTANG GERAKAN SOSIAL DI KEBUMEN - Danar Widiyanto (LPPM UNY, 2002)
Abstact OrganisasiAngkatan Oemat Islam (Islamic Community Movement Organization) in Kebumen at the commence of independence, 1945-1950, has performed a social movement having the character of religion. In order to be able to discuss a social movement we have to see essential component i.e. leadership, ideology and organization. Leadership of the Angkatan Oemat Islam centered mainly obb the personal authority of Kiai Haji Makhfudz Abdurrachman. Charisma of Kiai Haji Makhfudz Abdurrachman appeared among and moral courage. Ideologically Angkatan Oemat Islam as a stuggle agency could be identified as religious group in this case Islam. As a semimilitary body Angkatan Oemat Islam was founded on the Islamic religion.member of Angkatan Oemat Islam were largely santri with as main occupation farmer. The event of the social movement started by Angkatan Oemat Islam in Kebumen failed to reach its objective. This caused by the existence of various factors,firstly, the factor of human resources. Secoundly, the factor of facilities and pre-requirement relating to the question of funds, and the question of logistics/foods material and weapon owned by Angkatan Oemat Islam was not adequate for long term opposition. Thirdly, the psychological factor, at the time of the rebellion, Angkatan Oemat Islam must fight against their own friends during independence war, psychologically this was not advantageous although they had the belief that those they fought against was kafirs. Keywords: Angkatan Oemat Islam, Kebumen, and social Movement